Social Network Analysis for User Interaction Analysis on Social Media Regarding E-Commerce Business - Nugroho Agung Prabowo; Bambang Pujiarto; Firmantya Safri Wijaya; Lutfiana Gita; Denny Alfandy (International Journal of Informatics and Information Systems, 2021)
Abstract: E-commerce business requires promotion in introducing its products. One of the media that can be used is social media. There is a lot of information provided on social media, one of which is User Generated Content (UGC). UGC is a user's track record on social media that can be seen by other users. Social media analysis is needed to see the pattern of interaction between the company and its customers from UGC which is widely spread on social media. This can be used as an insight for companies in helping product marketing on social media. The method used in analyzing the interaction pattern of UGC in social media is Social Network Analysis (SNA). Social network modeling can help e-commerce businesses to understand the interaction patterns that occur on social media. The findings in this study show that the social network that is superior is the interaction social network regarding Lazada. Research also shows the key players for each e-commerce.